1994
DOI: 10.1002/hep.1840200107
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Antibiotic Therapy Prevents Bacterial Infection in Cirrhotic Patients With Gastrointestinal Hemorrhage

Abstract: This randomized prospective study was aimed at assessing the efficiency of a systemic antibiotic therapy for the prevention of bacterial infections in cirrhotic patients with gastrointestinal hemorrhage by ruptured esophageal varices. For 15 mo, all patients hospitalized with no infection on admission, were included in the study. Starting on admission day, patients in group A received ofloxacin (400 mglday) for 10 days, first intravenously then orally. They also received an intravenous bolus of amoxicillin plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
82
1
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(94 citation statements)
references
References 21 publications
7
82
1
4
Order By: Relevance
“…Indeed, early rebleeding in our study was significantly associated with infection (P = 0.042, \0.05). Bacterial infection occurs early in cirrhotic patients with variceal bleeding, and this finding is consistent with those of previous studies [13][14][15][16]. Our study revealed that enteric aerobic gram-negative bacteria are the most common causative organisms in patients with acute gastrointestinal bleeding.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, early rebleeding in our study was significantly associated with infection (P = 0.042, \0.05). Bacterial infection occurs early in cirrhotic patients with variceal bleeding, and this finding is consistent with those of previous studies [13][14][15][16]. Our study revealed that enteric aerobic gram-negative bacteria are the most common causative organisms in patients with acute gastrointestinal bleeding.…”
Section: Discussionsupporting
confidence: 94%
“…11,12,25 In addition, ischemia increases intestinal permeability to tions in ascitic rats undergoing HS, since it is known that in bleeding cirrhotic patients, infections occur macromolecules 12 and could promote the passage of endotoxins to portal and peripheral circulation-phe-within the first 10 days after HS. [1][2][3] In conclusion, the results of the present study sugnomena widely associated with BT. 26 As well, HS can impair the immune response, thus permitting the gest that HS further enhances BT in ascitic cirrhotic rats, and that SID is effective in decreasing this incispread of translocated bacteria.…”
supporting
confidence: 59%
“…9,10 The 3 raises the possibility that BT could be further enhanced already present in advanced cirrhotic subjects.…”
mentioning
confidence: 99%
“…Many clinical trials proved that prophylactic antibiotics with oral norfloxacin, intravenous ciprofloxacin, or ceftriaxone in cirrhotic patients with gastrointestinal (GI) bleeding can reduce infections and mortality [2][3][4][5]. Previous studies showed that enteric aerobic Gram-negative bacteria (GNB) are the most common causative organisms in patients with acute hemorrhage [2,3,[6][7][8]. However, there are some epidemiological changes in the etiology of infections because Gram-positive cocci (GPC) have markedly increased in cirrhotic patients, probably due to more invasive procedures in treating liver diseases in recent years [5].…”
Section: Introductionmentioning
confidence: 99%